(untitled) (GYMNASIUM, 2008)
In the sporting activity, muscular discrepancies are responsible for the installation of dysfunctions and lesions which come about as a consequence of overtraining the agonist muscles and ignoring the antagonist muscles. We chose exercises with the Klein gymball and Isostretching (Redondo, 2003), because the objectives of these methods are perfectly adapted to the special needs of our athletes. Only by taking these safety precautions and by correctly anticipating the dysfunctions, their causes and the moment in which they take place we shall obtain satisfactory results in the health and integrity of athletes.